2019
DOI: 10.1139/apnm-2018-0816
|View full text |Cite
|
Sign up to set email alerts
|

High doses of sodium nitrate prior to exhaustive exercise increases plasma peroxynitrite levels in well-trained subjects: randomized, double-blinded, crossover study

Abstract: The aim of this study was to investigate the effect of different doses of pre-workout sodium nitrate supplementation on nitric oxide, peroxynitrite levels, and performance parameters. Ten well-trained male subjects participated in a randomized, double-blinded, crossover study. They ingested 8, 16, and 24 mmol sodium nitrate or placebo (NaCl) dissolved in water at 2.5 h before an incremental exercise test. Respiratory gases (oxygen consumption, carbon dioxide production, respiratory exchange ratio) were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…In human studies, it has been confirmed that high‐intensity training increases oxidative stress 41–44 44 which may be involved in the progression of oxidative stress in SHR; our data regarding the detection of 3‐NT in the mesenteric artery further confirmed this conclusion. There are two free radical (FR) defence systems in the human body: an enzymatic defence system involving superoxide dismutase, glutathione peroxidase (GSH‐Px), catalase (CAT) and glutathione reductase (GR), and a non‐enzymatic defence system involving vitamin C, vitamin E and glutathione (GSH).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In human studies, it has been confirmed that high‐intensity training increases oxidative stress 41–44 44 which may be involved in the progression of oxidative stress in SHR; our data regarding the detection of 3‐NT in the mesenteric artery further confirmed this conclusion. There are two free radical (FR) defence systems in the human body: an enzymatic defence system involving superoxide dismutase, glutathione peroxidase (GSH‐Px), catalase (CAT) and glutathione reductase (GR), and a non‐enzymatic defence system involving vitamin C, vitamin E and glutathione (GSH).…”
Section: Discussionsupporting
confidence: 81%
“…HICT causes an increase in the level of vascular oxidative stress, leading to an increase in the ROS‐related uncoupling of eNOS, and the balance between NO and ROS is lost, which in turn causes a vicious cycle of reduced NO bioavailability and increased ROS 42 . In human studies, it has been confirmed that high‐intensity training increases oxidative stress 41–44 44 which may be involved in the progression of oxidative stress in SHR; our data regarding the detection of 3‐NT in the mesenteric artery further confirmed this conclusion.…”
Section: Discussionsupporting
confidence: 79%
“…We therefore measured plasma 3-NT concentrations, as another marker of the rate of NO production but also to determine whether the higher dose of NO 3 -(which averaged 28.7±2.7 mmol) resulted in "peaking over" of muscle contractile function due to an increase in nitrosative stress. This possibility was suggested by the recent results of Gholami et al (33), who reported that ingestion of 24, but not 8 or 16, mmol of NO 3 resulted in a dramatic increase in plasma peroxynitrite levels in well-trained subjects following a maximal incremental exercise test. In the present study, however, the pattern of change in plasma 3-NT instead generally resembled that of breath NO, i.e., tending to increase slightly after the lower dose but decrease slightly after the higher dose of NO 3 -.…”
Section: Discussionmentioning
confidence: 97%
“…Superoxide (a major ROS) reacts with NO and generates peroxynitrite (ONOO − ), an important oxidizing agent which causes critical damage to cells. Therefore, increased oxidative stress increases NO consumption and promotes peroxynitrite formation [ 37 ]. BMPRII, in turn, is involved in regulating angiogenesis, and proliferation and survival of endothelial cells.…”
Section: Deficiency In No Bioavailability and Activity In Cardiovascu...mentioning
confidence: 99%